The number of new disability benefit claimants has doubled in a year - Robert Joyce; Sam Ray-Chaudhuri; Tom Waters (Institute for Fiscal Studies (IFS), 2022)
Personal Independence Payment (PIP) is a disability benefit that aims to support individuals facing higher living costs due to difficulties in mobility or carrying out everyday tasks. In summer 2021, each month 15,000 or so working-age people started a PIP claim. That monthly figure had remained little changed for years. It then steadily increased, such that by July 2022 (the latest data) it had doubled to 30,000. This report investigates the increase.
Keywords: 330; Government finances and spending; Taxes and benefits; Benefits; Working age benefits; Health; Disability